2014
DOI: 10.2174/1871527313666140612123656
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and Suicide: A Systematic Review

Abstract: Suicide is considered a deliberate act initiated and concluded by a person with full knowledge or expectation of a fatal result, and one of the main symptoms of depression. An individual's conscious and excessive ingestion of a damaging substance is also considered to be an attempted suicide. Despite limited knowledge of caffeine abuse, deaths from overdose of caffeine have been reported in the literature. Thus, this study aims to review the existing literature on caffeine consumption and suicide attempts and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…However, the effects of these drinks on reducing fatigue and boosting energy are controversial and short-lasting [ 1 ]. Several studies have reported fatal effects of caffeine abuse including suicide, with some conflicting findings [ 7 ]; suicide attempts using high caffeine intoxication have been reported with blood caffeine concentrations reaching as high as 170 mg/l [ 8 ]. The main active compound of caffeine is one of the most popular substances worldwide, which has occasional potential to abuse [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of these drinks on reducing fatigue and boosting energy are controversial and short-lasting [ 1 ]. Several studies have reported fatal effects of caffeine abuse including suicide, with some conflicting findings [ 7 ]; suicide attempts using high caffeine intoxication have been reported with blood caffeine concentrations reaching as high as 170 mg/l [ 8 ]. The main active compound of caffeine is one of the most popular substances worldwide, which has occasional potential to abuse [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…By documenting the frequency of use, reported side-effects and motivations behind consumption, it was possible to compare the obtained results with those of similar profile abroad. A study of energy drink consumption among college students attending a central Atlantic University in the USA found higher use in that area, with 51% of college students reporting consuming more than one drink per month [23]. Socio-economic or advertising prevalence could be factors contributing to this discrepancy, and future studies may seek to include such data in the surveys.…”
Section: Discussionmentioning
confidence: 99%
“…This information is relevant for the administrators of such institutions as they seek to understand what factors encourage stimulant usage. A frequently reported reason for energy drink consumption in the USA was to co-consume with alcohol while partying [23]. The growing trend of using energy boosting dietary supplements together with alcohol while partying is an increasing problem, and a future Polish study would benefit from exploring this issue [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Death due to caffeine overdose is rare, due in part to its marked gastric irritation resulting in spontaneous emesis. Most of these cases are suicides and a recent review (Silva et al 2014) has demonstrated that, despite being an addictive substance and potentially fatal in higher doses, caffeine was still a rare factor in a number of studies concerning its relation with suicide attempts and death.…”
Section: Introductionmentioning
confidence: 99%